Contractual Requirements Review and Management - Manuela RUSU; Ilinca MARIN (SOARE); Valentin SOARE; Sergiu TONOIU; Ovidiu BLAJINA (INCAS Bulletin, 2022)
This article presents contractual requirements review as an element of a Quality Management System (SR EN 9100:2018 [1]), which requires the organization to conduct requirements reviews at various stages of the product realization lifecycle. Proper conduct of a review and management of requirements will enhance overall supply chain performance with regards to On-Time-On-Quality Delivery (OTOQD).